A Case of Intramuscular Cryptococcosis Mimicking a Malignant Tumor on FDG PET/CT. (July 2019) - Wang, Ling; Zheng, Xiangwu; Lin, Jie; Tang, Kun
Abstract : Abstract: Intramuscular cryptococcosis is extremely rare. In this case, a 76-year-old man with history of acute myeloid leukemia presented a painful mass in the right upper arm. FDG PET/CT demonstrated a low-density irregular-shaped mass in the triceps muscle of the right upper arm with adjacent bone erosion. The lesion presented with significantly increased activity with an SUVmax of 23.4, which could be misdiagnosed as a malignant tumor. The lesion was confirmed as cryptococcosis by periodic acid–Schiff stain and culture of biopsied specimen. Because cryptococcal infection is treatable, it is important to increase awareness of this hypermetabolic benign lesion in the unusual location.